Assessing mental health outcomes for residents of supported accommodation services: IJPDS (2017) Issue 1, Vol 1:204 Proceedings of the IPDLN Conference (August 2016) - Sims, Scott; Lima, Fernando; Moltoni, Michael; Harrison, Amanda; Glauert, Rebecca (International Journal of Population Data Science, 2017)
ABSTRACT Objectives Supported accommodation services provide housing for people with a severe and persistent mental illness; people who are homeless, at risk of homelessness, in unsuitable accommodation, or residing for long periods in inpatient units. The aim of this research is to examine the extent to which supported accommodation impacts on levels and costs of hospitalisation, utilisation of community based clinical services and mental health outcomes of present and past residents. Approach The research will make use of demographic data from supported accommodation services and Western Australian (WA) linked data from existing health data collections by the Data Linkage Branch WA Health. The data linkage methodology used involves the linking and analysis of data between 1997 and 2013 from a diverse number of datasets (Hospital Morbidity data, Mental Health Ambulatory data, Emergency data, Mortality data and Hospital Cost data). The impact of supported accommodation on individuals was measured by tracking any changes in their service utilisation levels and associated hospital costs savings. This allowed us to determine the efficacy of supported accommodation services through time series and control group comparative analysis. Results People with severe or persistent mental illness who reside in supported accommodation services are more likely to maintain or improve their quality of life and mental health outcomes compared to those who have never entered supported accommodation. Individuals who utilised these services also experienced reduced hospitalizations after the service than before. Cost implications will also be discussed. Conclusions No significant research into the effectiveness of supported accommodation on mental health outcomes for individuals has been conducted in WA to date. Supported accommodation provides people with severe and persistent mental illness, along with their families, carers and supporters, more security and control over their lives, and improved access to appropriate supports and clinical services. This research will support these strategic directions by providing evidence about the effectiveness of supported accommodation options in terms of improving mental health outcomes for individuals.